Serum butyrylcholinesterase activity as a predictor of severity and mortality in COVID-19 patients - Tomáš Fazekaš; Lucia Kováčik; Morteza Motahari Rad; Xavier Gabaldó Barrios; Simona Mihaela Iftimie; Jordi Camps; Anna Hrabovská (Scientific Reports)
Abstract Previous studies suggest that butyrylcholinesterase (BChE), an enzyme involved in the cholinergic anti-inflammatory pathway, may be linked to inflammation, disease severity, and risk of death in COVID-19 patients. Extending earlier work on BChE and COVID-19 severity, this study investigates additional factors such as age, sex, vaccination status, and symptom profiles. We analyzed 462 patients with polymerase chain reaction (PCR)-confirmed COVID-19 from the first epidemic wave in Spain, examining the association between BChE activity, clinical outcomes, demographic factors, and symptoms. The cohort consisted of 78 asymptomatic patients, 200 patients with mild symptoms, 122 patients with severe symptoms, and 62 critically ill patients. Of the patients in the severe symptoms group and critically ill patients, 26 died within 30 days of diagnosis. Our results showed that BChE activity was not affected by sex but decreased significantly with age (P < 0.0001). Patients with severe COVID-19 symptoms and critically ill patients exhibited lower BChE activity than asymptomatic or mildly symptomatic individuals (P < 0.0001). Furthermore, lower BChE activity was observed in patients with respiratory symptoms, such as pneumonia (P = 0.0027) and dyspnea (P = 0.0120), while higher BChE activity was seen in patients with neurological symptoms, such as anosmia (P < 0.0001), ageusia (P = 0.0012), and headache (P = 0.0005). No significant association was found between BChE activity and gastrointestinal, algesic, musculoskeletal, or systemic inflammatory symptoms. Additionally, vaccinated patients, particularly those who received two doses, had lower BChE activity compared to unvaccinated individuals (P = 0.0465). In conclusion, serum BChE activity is significantly associated with the severity, mortality, and specific symptoms of COVID-19, and is influenced by age and vaccination status. These findings imply that BChE may be a potential biomarker to support prognosis and risk stratification in COVID-19 patients. However, further research is needed to understand the underlying mechanisms and to validate the role of BChE in clinical practice.